2020
DOI: 10.1007/s13312-020-1961-0
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Outcome of SARS-CoV-2 Infection in Children: A Systematic Review and Meta-analysis

Abstract: W ith the rapidly evolving severe acute respiratory syndrome coronavirus-2 (SARS-Cov-2) pandemic, the knowledge about the disease manifestations and severity has also evolved quickly. Due to its resemblance to SARS, influenza, and other respiratory viruses, children were initially thought to be more susceptible than adults. However, less than 5% of total coronavirus disease (COVID-19) cases belong to the pediatric age group, and the severity has been milder as compared to adults [3,4]. Information regarding cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
107
7
7

Year Published

2020
2020
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(135 citation statements)
references
References 41 publications
14
107
7
7
Order By: Relevance
“…A multicentric study also showed milder form of the disease in children [ 8 ]. A recent meta-analysis has also shown that most of the patients have mild to moderate disease (96%) with only 1% of all the symptomatic paediatric cases being critically sick [ 9 ]. In children who were symptomatic, fever cough and rhinitis were common symptoms; similar findings being reported in a study from China [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…A multicentric study also showed milder form of the disease in children [ 8 ]. A recent meta-analysis has also shown that most of the patients have mild to moderate disease (96%) with only 1% of all the symptomatic paediatric cases being critically sick [ 9 ]. In children who were symptomatic, fever cough and rhinitis were common symptoms; similar findings being reported in a study from China [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…If small airways are predominantly affected, treatment modalities will include bronchodilators, corticosteroids, oxygen supplementation and respiratory support as required. However, bronchodilators are potentially detrimental in a scenario of alveolar disease due to pro-inflammatory effects on alveoli, worsening of ventilationperfusion mismatch and increased tachycardia [4]. There is no clear-cut separation of these phenotypes and overlap may be expected.…”
Section: Clinical Case Lettersmentioning
confidence: 99%
“…There is no clear-cut separation of these phenotypes and overlap may be expected. Corticosteroids, typically in courses longer than that used in exacerbations of asthma, are currently in use for treating severe COVID-19 [4,5]. The role of antiviral treatment is not precisely known especially in the pediatric context [4].…”
Section: Clinical Case Lettersmentioning
confidence: 99%
See 2 more Smart Citations